2022
DOI: 10.3390/hydrology9010015
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenic in Groundwater Using Fe(III) Oxyhydroxide Coated Sand: A Case Study in Mekong Delta, Vietnam

Abstract: Because of its threat to the quality of freshwater resources and human health, arsenic (As) pollution is important to scientific communities and policymakers around the world. The Mekong Delta, Vietnam, is one hotspot of As pollution. Its risk assessment of different environmental components has been well documented; however, very few studies focus on As removal techniques. Considering this information gap, this study aimed to investigate the performance of an innovative and low-cost treatment system using Fe(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…At lower concentrations, the linear segment of Langmuir and Freundlich isotherms is more pronounced. Kim et al [48] performed batch adsorption experiments with concentrations similar to the present study (110 µg/L) and found good fits with linear and non-linear (Langmuir and Freundlich) isotherms models. Table 3 summarizes the estimated parameters for the adsorption of arsenic onto Goethite-coated sand columns.…”
Section: Inverse Fittingsupporting
confidence: 73%
See 1 more Smart Citation
“…At lower concentrations, the linear segment of Langmuir and Freundlich isotherms is more pronounced. Kim et al [48] performed batch adsorption experiments with concentrations similar to the present study (110 µg/L) and found good fits with linear and non-linear (Langmuir and Freundlich) isotherms models. Table 3 summarizes the estimated parameters for the adsorption of arsenic onto Goethite-coated sand columns.…”
Section: Inverse Fittingsupporting
confidence: 73%
“…The adsorption column was modeled using a linear system form of the advectiondispersion equation (ADE) [47]. A two-site model with first-order kinetics was used to explain the adsorption of arsenic in Goethite-coated sands following [34,48]. This model assumes an equilibrium state at a fraction (f ) of Goethite-coated sand, while nonequilibrium exists at the rest of the adsorption sites [49].…”
Section: Modelingmentioning
confidence: 99%
“…However, in this study, it was indicated that adsorption of phosphate on TW-Fe 3 O 4 adsorbent is controlled by a pseudo-second-order reaction mechanism along with intra-particle diffusion. It is also noticeable from Figure 4d that the linear plot of intra-particle diffusion does not pass through the origin, which reveals that the mechanism of PO 4 3− adsorption on TW-Fe 3 O 4 is complex, and both the surface adsorption and intraparticle diffusion govern the rate-determining step [53].…”
Section: Application Of Kinetic Modelsmentioning
confidence: 95%
“…Over the years, a number of techniques have been developed to treat and purify waste and groundwater. Some of these techniques include solvent extraction, flotation, precipitation, oxidation, evaporation, adsorption, and membrane filtration [ 167 , 168 , 169 ]. Because of its cost effectiveness, operational ease, low energy consumption, superior efficiency, and availability of a diverse range of membrane materials, membrane filtration is considered one of the leading techniques used for water treatments.…”
Section: Applications Of Graphenementioning
confidence: 99%